Factors determining capital structure: a case study of listed companies in Sri Lanka. - Sangeetha, M.; Sivathaasan, N. (Research Journal of Finance and Accounting, 2013)
The most debatable topic in capital structure revolves around the optimal capital structure. This article investigates the factors determining capital structure in Sri Lankan context during 2002 to 2006 (five years). In an attempt, the present study examined the determinants of capital structure such as tangibility, size, growth rate, profitability, liquidity and dividend payout with samples of 50 companies including 13 sectors representing 21% of the mean number of companies listed in Colombo Stock Exchange Ltd as of 2006. Descriptive and inferential statistics were used in the analysis of data using Statistical Package for Social Science (SPSS). Results revealed that the use of debt capital is relatively low in Sri Lanka and size, growth rate and profitability are statistically significant determinants of capital structure. According to regression analysis, above six factors have an impact on capital structure at the rate of 77 % which is significant at 0.05 levels.
Keywords: Capital Structure; Determinant(s); Colombo Stock Exchange